Multiple positive solutions for quasilinear elliptic problems with sign-changing nonlinearities - Julián Fernández Bonder (Abstract and Applied Analysis)
Using variational arguments, we prove some nonexistence and multiplicity results for positive solutions of a system of p-Laplace equations of gradient form. Then we study a p-Laplace-type problem with nonlinear boundary conditions.